Papaya somatic embryogenic protocol - Almeida, Eliane Pires de; Oliveira, Roberto Pedroso de; Dantas, Jorge Luiz Loyola (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this work was to establish a protocol for somatic embryogenesis of papaya (Carica papaya L.) cv. Baixinho de Santa Amália, Solo group. Four explants and two culture conditions were used. The phases of callus induction, somatic embryo induction and development, elongation and rooting were evaluated in different culture media. The combination among hypocotyl with cotyledonal leaves, ½MS medium with 10 mg L-1 2.4-D and dark conditions was the best to induce friable calli. HMH medium with 0.2 mg L-1 ANA and 2.0 mg L-1 kinetin and ½MS medium were suitable to induce and to develop somatic embryos. MS medium with 1 mg L-1 GA3 was the best to elongate the plantlets and MS medium with 1 mg L-1 IBA to root them. The efficiency of callus induction, embryo induction, embryo development, elongation, rooting and acclimatization phases were 100%, 98%, 44%, 42%, 50% and 80%, respectively. The somatic embryogenic protocol enables the process to be done in 230 days with final efficiency of 7%. This protocol can be used in papaya genetic transformation.